Multi Cluster Monitoring for Fault Detection Using Novel Kubernetes with Prometheus over Docker Container (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to estimate the accuracy of Multi-Cluster Monitoring for fault detection using novel kubernetes with prometheus over docker containers. Materials and Methods: Sample groups that are considered in the project can be classified into two each has 20 samples, one for novel kubernetes with prometheus and other for docker containers, which are tested using 0.80 for G-power to determine the sample size and for t-test analysis. 5 Clusters have been used in each group for estimating the efficient accuracy. Results: The novel kubernetes with prometheus with efficient accuracy of 87.60%,which by far seems to be better than the docker containers which gives around 84.20%. The significance is around 0.034 (p<0.05) and therefore there is a statistical insignificant difference among the study group. Conclusion: Novel kubernetes with prometheus seem to be better in Multi-Clustermonitoring for fault detection over the docker containers.